Antibacterial activity of seed extracts of various species of the Annonaceae family cultivated in Colombia - Giraldo-Rivera, Ana Isabel; Guerrero-Álvarez, Gloria Edith (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
Public health concerns increase due to microbial propagation and the resistance to existing drugs; therefore, new alternatives are sought, such as the use of natural sources that are antimicrobial agents. Thus, the aim of this study was to evaluate the antibacterial potential of ethanolic extracts of seeds of the species Annona muricata (L.), Annona cherimola (Miller), Annona glabra (L.), Annona reticulata (L.), Rollinia mucosa ([Jacq.] Baillon) and Annona montana (Macfad.) of the Annonaceae family cultivated in Colombia. The bacterial strains correspond to: Staphylococcus aureus (Rosenbach), Enterococcus faecalis ([Andrewes and Horder] Schleifer and Kilpper-Bölz), Bacillus subtilis ([Ehrenberg] Cohn), Escherichia coli ([Migula] Castellani and Chalmers) and Pseudomonas aeruginosa ([J.Schröter] Migula). The antibacterial activity evaluation was performed using the agar diffusion method, each microorganism was inoculated in the medium in a concentration range of 0.2-0.5% v/v and the activity was measured by measuring the inhibition halo. A phytochemical assay was performed to identify the main metabolites to which the activity was attributed. Among the results obtained, it was found the extract of A. montana showed activity against the five bacterial strains, followed by A. glabra; the highest percentage of inhibition achieved was of A. cherimola with 79.86±3.81% activity against E. faecalis; A. reticulata and R. mucosa presented susceptibility only against two bacterial strains, the contrary, the extract of A. muricata did not present any response. The main types of metabolites identified and those attributed to antibacterial potential corresponded to alkaloids, saponins and terpenoids. The above indicates that the plants extract of Annonaceae showed antimicrobial effects. This suggest that species of this family are potential sources of compounds with antibacterial properties, which broadens the knowledge of natural extracts of Colombian materials for use in pharmacotherapy and as alternative for synthetic antibacterial agents.